2018
DOI: 10.3991/ijim.v12i3.8219
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Academic Writing in a Mobile Skype-Based Blended Model

Abstract: <p class="Default"><strong>Background</strong>: Web media like Skype, Twitter, WhatsApp, and SMS not only make it viable to deliver, receive and share educational information, but to simplify communication with other people in various skills such as writing, link sharing, and voice or video files. There are three areas addressed to direct the plan and implementation of this survey as main objectives:</p><p>the faculty members' feelings and impression on applying Skype site as a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Apparently, educators and students are becoming more and more familiar with online platforms in participating in teaching and learning activities via various online platforms such as Google Meet, Author and Skype. Research has shown that language students using technology and social media sources possess more advantages in terms of the four language skills (listening, reading, writing, and speaking) in English [13]. Apparently, students with access to online learning possess wider command of vocabulary and deeper conceptual understanding of English language including grammar rules due to the continuous practice of using online approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apparently, educators and students are becoming more and more familiar with online platforms in participating in teaching and learning activities via various online platforms such as Google Meet, Author and Skype. Research has shown that language students using technology and social media sources possess more advantages in terms of the four language skills (listening, reading, writing, and speaking) in English [13]. Apparently, students with access to online learning possess wider command of vocabulary and deeper conceptual understanding of English language including grammar rules due to the continuous practice of using online approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there are several research studies on using Google Docs for improving organization, content, spelling, punctuation, grammar, and sentence structure, they mostly focus on investigating the effect of peer tutoring and motivation on developing collaborative writing skills of learners via Google Docs (Abrams, 2019;Alharbi, 2020;Alsubaie & Ashuraidah, 2017;Lin & Yang, 2013;Suwantarathip & Wichadee, 2014). The current paper also concentrates on Google Docs but displays differences with previous research in terms of research design, research questions, and data collection tools (Ambrose & Palpanathan, 2017;Arani, 2018;Aşıksoy, 2018;Cunningham, 2000;Khodabandeh & Soleimani, 2018). It should be noted that peer tutoring was not emphasized in this study; instead, each student worked independently and received individual feedback via Google Docs.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Saudi Arabia discussed the effect of using SMS message apps and social media through mobile apps on Saudi students' academic writing, and indicated that although mobile phone usage played a role in improving comfort while working and shortened the time required to complete academic tasks, it also affected students' ability to spell words correctly and build sentences within their academic reports [37]. On the other hand, other studies have discussed the use of mobile apps in teaching, learning, and improving the language skills of students, including their writing [20,[38][39][40][41][42][43]. For instance, one study stated that using mobile apps such as SMS message apps and email for educational purposes has improved the academic writing of students, especially in terms of grammar and vocabulary [44].…”
Section: Introductionmentioning
confidence: 99%